Morning versus evening supplementation for heifers grazing winter range - E. Vanzant; B. Cochran; L. Corah; K. Zoellner (Kansas Agricultural Experiment Station Research Reports, 1988)
Supplementing developing heifers in the morning was compared with supplementation at sundown. No difference was evident among treatments in average daily gain, distance traveled, or time spent grazing.
Keywords: Kansas Agricultural Experiment Station contribution; no. 88-363-S; Cattlemen' s Day; 1988; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 539; Beef; Morning vs. evening grazing; Heifers